Theory/praxis confusion within Irish Liberalism: The curious case of teenage sexuality. (December 2017) - Foley, Simon
The contention that non-procreational sex is inherently sinful is a basic tenet of Catholic teaching. From a secular liberal perspective this proposition is inverted. Yet, despite this ideological clash, in 21st century Ireland there exists a unique convergence of views between members of these opposing ideologies when answering the questions as to whether teenagers under 17 should be allowed to control their sexuality and whether it is right to conceive of female teenagers under 17 as less autonomous and less sexual than their male counterparts. Utilizing an ideal type 'Irish secular liberal' construction, this article, deploying insights from the Foucauldian framework, problematizes the secular liberal response to a series of related issues revolving around the rights of Irish teenagers to control their sexuality. It argues that the Irish secular liberal regulation of teenage sexuality by reference to the cognitive ability/sexual autonomy discourse is not the product of a reflexive concern with the psychological harm that may ensue if underage teenagers engage in sexual relations. Rather, it advances the theory that such surveillance, both internal and external, is primarily a means through which the responsible heteronormative adult subject position is produced and governed.